2021
DOI: 10.1039/d1fo02453a
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin activity as a function of pH and digestion time on caseins and egg white proteins under static in vitro conditions

Abstract: The activity of pepsin, the gastric protease, is generally considered to be negligible for pH ≥ 4, based on results obtained with few purified globular proteins. The present study aimed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 50 publications
(82 reference statements)
2
20
0
Order By: Relevance
“…Although the characteristic bell-shaped curve remained the same for casein substrate 40 as other substrates, we note that the activity change with pH observed in this study on hemoglobin was slightly less than that observed in previous studies for different such as chicken or ostrich substrates; for example, at pH 3 the activity of pepsin on hemoglobin was observed to drop by only 30% in our study (compared to a drop of 60-70% observed in previous studies with other substrates) [45][46][47] . However, we note that these previous studies evaluating pepsin activity as a function of pH employed slightly different methodologies and used different substrates 40 and sources of pepsin such as chicken 45 or ostrich 46 .…”
Section: Pepsin Activity and Solubilitymentioning
confidence: 85%
See 3 more Smart Citations
“…Although the characteristic bell-shaped curve remained the same for casein substrate 40 as other substrates, we note that the activity change with pH observed in this study on hemoglobin was slightly less than that observed in previous studies for different such as chicken or ostrich substrates; for example, at pH 3 the activity of pepsin on hemoglobin was observed to drop by only 30% in our study (compared to a drop of 60-70% observed in previous studies with other substrates) [45][46][47] . However, we note that these previous studies evaluating pepsin activity as a function of pH employed slightly different methodologies and used different substrates 40 and sources of pepsin such as chicken 45 or ostrich 46 .…”
Section: Pepsin Activity and Solubilitymentioning
confidence: 85%
“…The porcine pepsin (EC 3.4.23.1) activity was determined using the protocol of INRAE-STLO as described in Salelles, et al 40 in 100% H 2 O and 100% D 2 O. In brief, bovine blood hemoglobin (2%, (w/v)) was used as a substrate.…”
Section: Pepsin Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…pathogenicity ( De Sousa-Carvalho et al, 2011 ), it was of interest to analyze also the influence of collagenase on A. castellanii excystment. In addition, pepsin was used in non-optimal conditions, at pH 6.5, which is distant from its optimal pH at 2 and where only a residual activity has been previously observed ( Salelles et al, 2021 ), thus favoring a gentle digestion of the FLA cyst wall. Indeed, at pH 2, no excystment was observed in our conditions after an incubation of up to 18 days at 30°C in the presence of 100 U/mL pepsin, while the amoebae were able to excyst after a treatment in the same conditions at pH 2 without the enzyme, showing a cysticidal effect of pepsin at pH 2 on A. castellanii .…”
Section: Discussionmentioning
confidence: 99%